Case report: Salivary duct carcinoma in a patient with a germline CDH1 pathogenic variant - expanding the spectrum of hereditary cancer predisposition syndromes - Desai, Nidhi; Racila, Emilian; Fujioka, Naomi; Gupta, Arjun; Antonarakis, Emmanuel S. (Frontiers in Oncology, 2024)
Recently, an entity known as salivary duct carcinoma with rhabdoid features (SDC-RF) has been associated with somatic CDH1 mutations. Here we present the first known case report of conventional SDC occurring in the setting of a germline CDH1 pathogenic variant accompanied by a somatic loss of heterozygosity at the CDH1 locus.Case Discussion: A 67-year-old man presented with chest and back pain and was found to have osteolytic lesions in sternum and lumbar spine. Vertebral bone biopsies were positive for metastatic carcinoma of unknown primary. A molecular profiling assay consisting of both whole-exome next-generation sequencing (NGS) as well as immunohistochemistry (IHC) for select clinically-relevant proteins performed on the bone biopsy suggested a triple-negative (ER/PR/ERBB2 negative, by IHC), androgen receptor (AR IHC) positive tumor profile.Additionally, the assay uncovered a coding mutation in the CDH1 gene (c.1792C>T, p.R598*) with genomic loss of the second CDH1 allele. Germline testing returned positive for a heterozygous CDH1 pathogenic variant. PET-CT revealed a tumor in the neck suggestive of the primary malignancy consistent with that of salivary gland origin. The patient was initially treated with carboplatin and paclitaxel, then pembrolizumab, and finally with AR-directed therapy using leuprolide and enzalutamide. These treatments were not successful, and the patient eventually succumbed from his disease.Molecular testing revealed our patient had bi-allelic inactivation of the CDH1 gene. We believe our patient developed a somatic mutation in addition to his preexisting germline CDH1 mutation that ultimately predisposed him to SDC. While previous studies have found somatic CDH1 pathogenic variants in SDC-RF, our patient was found to have a germline CDH1 pathogenic variant in the setting of conventional SDC, without rhabdoid features. This case provokes questions regarding tumor genetics and molecular profiling of SDC in patients with germline CDH1 pathogenic variants. Moreover, this case supports the notion that SDC may be the salivary counterpart of other malignancies associated with germline CDH1 pathogenic variants and may possibly expand the spectrum of tumors that arise in this familial cancerpredisposition syndrome.